Monitoring Ekspresi Gen Chalcone Synthase dan Respon Pertumbuhan Lobak Singgalang (Brassica oleracea L.) Akibat Paparan Ultraviolet-B Ekstrem - Amar, Puti Khairunnajwa; Mansyurdin, Mansyurdin; Syafni, Nova; Syafia, Ersa Nur; Idris, Muhammad (Universitas Gadjah Mada, 2025)
Singgalang cabbage (Brassica oleracea L.) is a local vegetable native to West Sumatra, cultivated in highlands around Mount Singgalang, Tanah Datar. Vegetables from Brassica genus are recognized for their high nutritional value and potential as functional foods. Key secondary metabolites in Brassica species, i.e., phenolic compounds and their derivatives, play a crucial role in antioxidant activity and are essential in promoting health. Light exposure, particularly ultraviolet-B (UV-B, 280-315 nm), can enhance biosynthesis of these compounds. UV-B intensity affects various process in plants including the phenylpropanoid pathway involved in secondary metabolite production. This study aimed to assess the expression of the CHALCONE SYNTHASE (CHS) gene under different UV-B intensities (0.3–3.0 µmol·m-2·s-1, 4 h) and examine the effects of two extreme UV-B intensities (0.3 and 3.0 µmol·m-2·s-1, 4h.d-1) in a controlled environment for 14 days. The results showed that increasing UV-B intensity enhanced CHS expression (1.0 and 3.0 µmol·m-2·s-1 showed thicker bands compared to 0.3 µmol·m-2·s-1, with a faint band in the control). Extreme UV-B exposure reduced chlorophyll content by 35–37% compared to the control, while carotenoids remained unaffected. Anthocyanin accumulation increased under low-intensity UV-B, whereas flavonoid levels were higher under high-intensity UV-B, suggesting different functional roles. UV-B exposure also influenced stomatal number and density in leaf. This preliminary study highlights the significant role of UV-B in enhancing specific metabolites in Singgalang cabbage, supporting its potential as a functional food.